2017
DOI: 10.1021/acs.nanolett.7b03405
|View full text |Cite
|
Sign up to set email alerts
|

Remote Manipulation of Ligand Nano-Oscillations Regulates Adhesion and Polarization of Macrophages in Vivo

Abstract: Macrophages play crucial roles in various immune-related responses, such as host defense, wound healing, disease progression, and tissue regeneration. Macrophages perform distinct and dynamic functions in vivo, depending on their polarization states, such as the pro-inflammatory M1 phenotype and pro-healing M2 phenotype. Remote manipulation of the adhesion of host macrophages to the implants and their subsequent polarization in vivo can be an attractive strategy to control macrophage polarization-specific func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
69
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 54 publications
0
69
1
Order By: Relevance
“…Beside, it has been demonstrated that RGD‐conjugated rod‐like viral nanoparticles coated on substrates promoted the osteogenesis . We previously achieved magnetic control over the tether mobility of RGD peptide‐bearing magnetic nanoparticles conjugated to substrates through flexible poly(ethylene) glycol linkers, and this manipulation of the nanoscale presentation of the cell adhesive ligand by nanomaterials regulates the adhesion and differentiation of stem cells and polarization of macrophages . Nevertheless, few studies have investigated the effects and mechanism of anisotropic nanofeature‐mediated recruitment, and the distribution of different integrin subtypes of cells is an important missing link in elucidating the molecular interactions between cells and nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Beside, it has been demonstrated that RGD‐conjugated rod‐like viral nanoparticles coated on substrates promoted the osteogenesis . We previously achieved magnetic control over the tether mobility of RGD peptide‐bearing magnetic nanoparticles conjugated to substrates through flexible poly(ethylene) glycol linkers, and this manipulation of the nanoscale presentation of the cell adhesive ligand by nanomaterials regulates the adhesion and differentiation of stem cells and polarization of macrophages . Nevertheless, few studies have investigated the effects and mechanism of anisotropic nanofeature‐mediated recruitment, and the distribution of different integrin subtypes of cells is an important missing link in elucidating the molecular interactions between cells and nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Except for regulating stem cells, MN‐based strategy can also manipulate the function of other cell types, including macrophages, Chinese hamster ovary (CHO) cells, cochlear hair cells, and cortical neurons . Bian and co‐workers reported that MNs‐RGD with a diameter <20 nm were able to manipulate macrophage adhesion and polarization via delivering oscillation toward cell membrane .…”
Section: Mn‐based Mechanotransduction For Cell Fate Regulationmentioning
confidence: 99%
“…Except for regulating stem cells, MN‐based strategy can also manipulate the function of other cell types, including macrophages, Chinese hamster ovary (CHO) cells, cochlear hair cells, and cortical neurons . Bian and co‐workers reported that MNs‐RGD with a diameter <20 nm were able to manipulate macrophage adhesion and polarization via delivering oscillation toward cell membrane . Magnetic oscillation of low‐frequency MNs‐RGD enhanced adhesion of macrophages and stimulated polarization toward the M2 phenotype whereas under a high oscillation frequency, macrophages tended to be less adhesive and polarized to the M1 phenotype …”
Section: Mn‐based Mechanotransduction For Cell Fate Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the Bian group reported the successful modulation of adhesion and polarization with magnetically responsive substrates implanted in mice. [45••–46]…”
Section: Introductionmentioning
confidence: 99%